Treatment with a corticotrophin releasing factor 2 receptor agonist modulates skeletal muscle mass and force production in aged and chronically ill animals - Ferreira Leonardo F (BMC Musculoskeletal Disorders, 2011)
Abstract Background Muscle weakness is associated with a variety of chronic disorders such as emphysema (EMP) and congestive heart failure (CHF) as well as aging. Therapies to treat muscle weakness associated with chronic disease or aging are lacking. Corticotrophin releasing factor 2 receptor (CRF2R) agonists have been shown to maintain skeletal muscle mass and force production in a variety of acute conditions that lead to skeletal muscle wasting. Hypothesis We hypothesize that treating animals with a CRF2R agonist will maintain skeletal muscle mass and force production in animals with chronic disease and in aged animals. Methods We utilized animal models of aging, CHF and EMP to evaluate the potential of CRF2R agonist treatment to maintain skeletal muscle mass and force production in aged animals and animals with CHF and EMP. Results In aged rats, we demonstrate that treatment with a CRF2R agonist for up to 3 months results in greater extensor digitorum longus (EDL) force production, EDL mass, soleus mass and soleus force production compared to age matched untreated animals. In the hamster EMP model, we demonstrate that treatment with a CRF2R agonist for up to 5 months results in greater EDL force production in EMP hamsters when compared to vehicle treated EMP hamsters and greater EDL mass and force in normal hamsters when compared to vehicle treated normal hamsters. In the rat CHF model, we demonstrate that treatment with a CRF2R agonist for up to 3 months results in greater EDL and soleus muscle mass and force production in CHF rats and normal rats when compared to the corresponding vehicle treated animals. Conclusions These data demonstrate that the underlying physiological conditions associated with chronic diseases such as CHF and emphysema in addition to aging do not reduce the potential of CRF2R agonists to maintain skeletal muscle mass and force production.